Schedule management of a company that manufactures, assembles and installs electrical harness which services the civil construction sector - Athanazio, Felipe Paganini; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2023)
This article aims to present proposals for improvements in the time management process of a company that manufactures, assembles and installs electrical harnesses that serves the construction sector. The methodology used has a qualitative approach and technical case study procedure. Data collection was carried out through bibliographical research and field interviews with professionals directly involved in the investigated project. The main results were the notes on proposals for improvements in project time management, ensuring greater organizational effectiveness, such as: better dissemination of the manufacturing process, assembly and installation of industrialized electrical harnesses, development of a calendar with delivery information and manufacturing time, presentation of the minimum information necessary for estimating task durations, allocating more time and dedication to create the most detailed and structured schedule, and using the most appropriate technology to improve the information in the process of quantitative surveying of materials, reducing the rate of verification rework, which increases the effectiveness of the company's warehouse process.
Keywords: Electrical planning and transformation; calendar; process control; production time